Al Ma’un Values in Developing Social Attitudes of Muhammadiyah Students: Nilai-nilai Al Ma’un dalam Pembentukan Sikap Sosial Mahasiswa Muhammadiyah - Abdullah, Latiefa Diah; Amrullah, Muhlasin (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Education plays a crucial role in shaping balanced human character that integrates intellectual, emotional, and social dimensions. Specific background: In the context of Islamic education, QS. Al-Ma’un emphasizes empathy, caring, tolerance, and social responsibility, values highly relevant for elementary education within Muhammadiyah schools. Knowledge gap: Although studies on Islamic character education exist, few specifically explore the implementation of QS. Al-Ma’un in primary Muhammadiyah schools. Aims: This study aims to analyze how the values of QS. Al-Ma’un are applied to strengthen students’ social attitudes and religious character. Results: Using a qualitative case study approach with interviews, observations, and documentation, the findings reveal that students consistently demonstrated empathy, cooperation, tolerance, politeness, and environmental responsibility in daily school activities. Novelty: The research highlights the integration of QS. Al-Ma’un values into school routines as a practical framework for nurturing social character at an early educational stage, with a focus on Muhammadiyah schools. Implications: These findings suggest that embedding Al-Qur’anic values through habituation and teacher modeling not only reinforces religious behavior but also cultivates harmonious social interactions, offering practical insights for strengthening Islamic character education in contemporary elementary settings.Highlights: Strengthening students’ religious character through QS. Al-Ma’un values. Developing empathy, tolerance, and responsibility in daily school life. Habituation as an effective strategy for shaping social attitudes. Keywords: Al-Ma’un, Social Attitudes, Religious Character, Muhammadiyah Education, Elementary Students